Non-biaryl atropisomerism at the C–B bond in sterically hindered aminoarylboranes. Issue 16 (7th April 2020) - Birepinte, Mélodie; Robert, Frédéric; Pinet, Sandra; Chabaud, Laurent; Pucheault, Mathieu
Abstract : Sterically hindered aminoarylboranes with atropisomerism about the C–B bond were prepared and resolved by chiral stationary phase HPLC. Abstract : Sterically hindered aminoarylboranes featuring atropisomerism about the C–B bond were prepared by addition of organomagnesium species onto readily accessible dialkylamine–borane complexes. Some of these aminoarylboranes, isosteres of vinyl styrene derivatives, were resolved by HPLC on the chiral stationary phase. They are the first examples of a non-biaryl type system which display slow rotation about a C–B bond.